Dogs and puppies - Hill, Rose.; Keenan, Elaine Faris (Tulsa, Okla. : Usborne : EDC, 1982)
Discusses choosing a dog and the training and care of puppies and dogs.
3.5
K-3
Keywords: Dogs -- Juvenile literature; Dogs; Dogs